Backing up Lightroom - Kloskowski, Matt (Kelbytraining.com, 2010)
"Lightroom has become the total package for photographers right? We can import, sort and organize our photos. We use it to develop and process, and we can print or create websites. However, as important as our photos are, Lightroom doesn't really offer an out-of-the-box backup solution. That's exactly what we'll cover in this class"--Resource description page.